SIRT1/FOXO1 Axis-Mediated Hippocampal Angiogenesis is Involved in the Antidepressant Effect of Chaihu Shugan San - Zhang S; Lu Y; Shi W; Ren Y; Xiao K; Chen W; Li L; Zhao J (Dove Medical Press, 2022)
Shan Zhang,1 Yujia Lu,1 Wei Shi,1 Yi Ren,1 Kaihui Xiao,1 Wei Chen,2 Li Li,1 Jingjie Zhao1,3 1Department of Traditional Chinese Medicine, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 2Experimental and Translational Research Center, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 3Department of Integrated Traditional and Western Medicine, Capital Medical University, Beijing, 100050, People's Republic of ChinaCorrespondence: Jingjie Zhao, Beijing Friendship Hospital, Capital Medical University, No. 95 Yong-an Road, Beijing, 100050, People's Republic of China, Tel/Fax +86 10-63139096, Email zhaojj@ccmu.edu.cnObjective: Chaihu Shugan San (CSS) has a long history for treating major depressive disorder (MDD), which has been verified effectively and safely in clinical studies. Deficient angiogenesis plays important roles in MDD. However, the underlying mechanisms of CSS on angiogenesis remain poorly understood.Methods: Network pharmacology analysis was applied to explore the potential angiogenic targets and pathways between CSS and MDD. These targets would be validated in chronic unpredictable mild stress (CUMS)-induced depressive-like mice by Western blots, immunofluorescence, and immunohistochemistry. Then, the underlying molecular mechanisms were further investigated in brain microvascular endothelial cells (BMVECs) with CSS-containing serum by Western blots and immunofluorescence.Results: Network pharmacology analysis showed that the antidepressant role of CSS was closely associated with Silent information regulator protein 1 (SIRT1)/Forkhead box O1 (FOXO1) axis-mediated angiogenesis. This prediction was confirmed in the following experiments. CSS induced angiogenesis, increased SIRT1 expression, and decreased FOXO1 expression in the hippocampus of CUMS mice. Five percent CSS-containing serum produced a significant increase in BMVECs proliferation, migration, and tube formation, but these effects were reduced by SIRT1 silencing. CSS serum could also promote FOXO1 translocation to the cytoplasm through SIRT1 signaling, which triggered FOXO1 protein degradation. What is more, CSS upregulated VEGFA and BDNF expressions not only in the hippocampus of depressive mice but also in BMVECs supernatants. Of note, these trophic factors play important roles in promoting neurogenesis.Conclusion: The study showed that CSS could promote angiogenesis and neurogenesis in the hippocampus of CUMS-induced mice. The underlying molecular mechanism involves the SIRT1/FOXO1 axis and subsequent regulation of VEGFA and BDNF. These findings provide novel insight into CSS drug development, and targeting the SIRT1/FOXO1 axis might be a promising strategy to treat MDD.Graphical Abstract: Keywords: major depressive disorder, Chaihu Shugan San, SIRT1/FOXO1 axis, angiogenesis, brain microvascular endothelial cell